VIABILITAS BENIH SEBAGAI INDIKATOR TINGKAT PENCEMARAN LINGKUNGAN - Jumini Jumini (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2006)
Seed Vibility As An Indicator of Environmental Pollution Level Jumini ABSTRACT Germination of some seed species are very sensitive to environmental conditions and it could be used as an indicator of pollution level. The aim of this research was to study the viability of seeds of some species on some environmental pollution levels caused by lubricant waste. Units of this research were arranged by Factorial Randomized Completely Block Design with 3 replicates. Four levels of lubricant waste were 0, 1, 2 and 3 ppm, and 3 levels of seed species were spinach, mungbean, and soybean. The results showed that seed germination rate was very significantly affected by lubricant waste. The viability of spinach, mungbean, and soybean seeds pointed by seed germination rate could be an indicator of environmental pollution level caused by lubricant waste by equation; Y = 39.19 – 2,15x with r = -0.87. Potential germination, germination rate, seedling vigor, and seedling dry mass very significantly affected by seed species, but not on germination capacity. There were no significant interactions between the two treatments on all parameters observed.